The Study of the Game Addiction Problem Solving Needs and the Relationship between Personal Factor and Perception of Game Addiction Behaviors among School Age Children in Muang District, Phitsanulok Province - Sribuarom, Nittaya; Waencwaen, Namphon (NU Journal of Nursing and Health Sciences, 2023)
The purpose of this descriptive research study was to (1) explore the perceptions of children ‘s game addiction behaviors and the needs for problem solving of game addiction among school-age children and their parents and (2) examine the relationships among personal factor and children’s perceptions of game addiction. The study sample were students aged 10-15 years who are studying in the second semester of the academic year 2021 in the opportunity expansion schools located in Muang District, Phitsanulok Province. The sample size were 250 children and 250 children’s parents. The research instruments consist of: (1) personal data, (2) Child and Parent Version of Game Addiction Screening Test (GAST) for children and parents (Standard research instrument) reliability which were 0.87, 0.89, respectively, (3) Perceived Behavior Questionnaire Child and Parents Problem Solving Game Addiction Needs Questionnaire. The tools were assessed content validity which were 0.78, 0.82 and reliability which were 0.81, 0.86, respectively. Data were analyzed by using descriptive statistics including frequency, percentage, mean, and standard deviation, and eta coefficient, spearman rank correlation coefficient statistics which used to examine the relationships among personal factor and children’s perceptions of game addiction. The study results revealed that (1) most of school-age children (65.2 %) had normal level of perception of their gaming behaviors. While female students had perception of their game addiction at the level of mania for 20.6 % and likely to be addicted to games for 14.0 %, 28.1% consistent of boys perceived game addiction and likely to be addicted to games for 7.0 % . In contrast to for parents’ perceptions, they reported that game addiction of their children at the level of addicted game for 20.0 % which likely to be addicted to the game and 18.8 % at the level of madness. Whereas school-age children reported the greatest need for emotional support, their parents reported the highest need for support in assessment especially which to provide feedback and (2) from the study of correlation variables, it was found that gender, educational